An evaluation of the City of Cape Town Municipality's waste wise sustainable education and school recycling programme - Armien-Ally, Jameyah (Institute for Monitoring and Evaluation, 2014)
This dissertation examines the City of Cape Town municipality's Waste Wise Programme. It examines one of the three models, namely the Sustainable Education and School Recycling model and consists of a theory as well as a process evaluation. On commencement of the theory evaluation, the evaluator investigated the plausibility of the programme theory. In order to extract this information, a literature review on international and local literature was completed to answer the evaluation questions. The literature review suggests that the programme theory is plausible but that it could be further enhanced by incorporating a few additions to the programme. It investigated the Waste Wise Programme's impact theory, the service utilisation and the organisational plans, and found that, with a few minor amendments, the beneficiaries of the programme may benefit more.